Serviços e infraestrutura em mobilidade urbana: Alternativas de implementaç\~ao e financiamento - Adriano Paranaíba; Nilo Luiz Saccaro Júnior (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– The aim of this text is to describe and discuss alternatives for new urban mobility services and alternatives for financing the urban infrastructure associated with mobility. It is considered that urban mobility depends not only on services but also on adequate urban infrastructure. Alternatives are addressed, in a non-exhaustive manner, for: i) regulatory modernization of new mobility services; ii) infrastructure financing; and iii) tax collection directly associated with the service and urban furniture.
Keywords: H20; H71; O18; R14; R42; 330; urban mobility; infrastructure; micromobility; improvement contribution